Anti-breast Cancer Enhancement of a Polysaccharide From Spore of Ganoderma lucidum With Paclitaxel: Suppression on Tumor Metabolism With Gut Microbiota Reshaping - Su, Jiyan; Li, Dan; Chen, Qianjun; Li, Muxia; Su, Lu; Luo, Ting; Liang, Danling; Lai, Guoxiao; Shuai, Ou; Jiao, Chunwei; Wu, Qingping; Xie, Yizhen; et al. (Frontiers in Microbiology, 2018)
Increasing evidence highlights the cardinal role of gut microbiota in tumorigenesis and chemotherapy outcomes. Paclitaxel (PTX), although as a first-line chemotherapy reagent for breast cancer, still requires for improvement on its efficacy and safety due to drug resistance and adverse effects. The present work explored the enhancement of a polysaccharide derived from spore of Ganoderma lucidum (SGP) with PTX in a murine 4T1-breast cancer model. Results showed that the combination of PTX and SGP displayed an improved tumor control, in which mRNA expression of several Warburg effect-related proteins, i.e. glucose transporter 3 (Glut3), lactate dehydrogenase A (Ldha), and pyruvate dehydrogenase kinase (Pdk), and the metabolite profile of tumor was evidently altered. . Flowcytometry analysis revealed that the combination treatment recovered the exhausted tumor infiltration lymphocytes (TILs) via inhibiting the expressions of immune checkpoints (PD-1 and Tim-3), while PTX alone evidently increased that of CTLA-4. 16S rRNA sequencing revealed a restoration by the combination treatment on gut microbiota dysbiosis induced by PTX, especially that Bacteroides, Ruminococcus and other 5 genera were significantly enriched while the cancer-risk genera, Desulfovibrio and Odoribacter, were decreased. Moreover, spearman correlation analysis showed that abundance of Ruminococcus was significantly negative-associated with the amount of frucotose-6-phosphate within the tumor. Collectively, the present study suggests the clinical implication of SGP as an adjuvant candidate for PTX against breast cancer, which possibly relies on the regulation of tumor metabolism and gut microbiota.